Airway Epithelial Repair by a Prebiotic Mannan Derived from Saccharomyces cerevisiae. (9th July 2017) - Michael, Christie F.; Waters, Christopher M.; LeMessurier, Kim S.; Samarasinghe, Amali E.; Song, Chi Y.; Malik, Kafait U.; Lew, D. Betty
Abstract : In asthmatic airways, repeated epithelial damage and repair occur. No current therapy directly targets this process. We aimed to determine the effects of mannan derived from S. cerevisiae (SC-MN) on airway epithelial wound repair, in vitro . The presence of functional mannose receptors in bronchial epithelial cells was shown by endocytosis of colloidal gold-Man BSA via clathrin-coated pits in 16HBE cells. In primary normal human bronchial epithelial cells (NHBEC), SC-MN significantly facilitated wound closure. Treatment with SC-MN stimulated cell spreading as indicated by a significant increase in the average lamellipodial width of wound edge 16HBE cells. In addition, NHBEC treated with SC-MN showed increased expression and activation of Krüppel-like factors (KLFs) 4 and 5, transcription factors important in epithelial cell survival and regulation of epithelial-mesenchymal transition. We conclude that SC-MN facilitates wound repair in human bronchial epithelium, involving mannose receptors.